Biological science - Freeman, Scott (Prentice Hall, 2002)
This book helps its readers learn to think like biologists and gives them the tools they need for success in understanding more advanced subjects. A nine-part organization covers topics under the general headings of: the origin and early evolution of life, cell functions, gene structure and expression, developmental biology, evolutionary patterns and processes, the diversification of life, how plants work, how animals work, and ecology